Pengaruh Terapi AAROM dan Diet Rendah Karbohidrat Terhadap Penurunan Kadar Glukosa Darah pada Lansia Penderita DM Tipe II di Desa Ngepoh - Hoyriyetus Sholehah; Dodik Hartono; Achmad Kusyairi (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
Diabetes Mellitus is a disease characterized by hyperglycemia and metabolic disorders in the body which are associated with a lack of insulin secretion. Generally, DM therapy can be carried out using pharmacology and non-pharmacology. Non-pharmacological therapy that can be carried out is AAROM therapy and a low carbohydrate diet. The aim of this study was to determine the effect of AAROM therapy and a low carbohydrate diet on reducing blood glucose levels in elderly people suffering from type 2 DM in Ngepoh Village. This type of research isPre-experimentalby designTwo groups pre-post test. The total population was 90 respondents and the sample size was 33 elderly respondents suffering from type 2 DM in Ngepoh Village which were taken by purposive sampling. Data collection in this research used questionnaires and observation sheets. Analyzed with SPSS 20 using testsMan Whitney. The results of this study showed that the average blood glucose value in the control group was 282 mg/dl pre glucose and 177 mg/dl post glucose. Meanwhile, the mean blood glucose value in the treatment group with pre glucose was 295 mg/dl and post glucose was 144 mg/dl and there was an effect of AAROM therapy and a low carbohydrate diet on reducing blood glucose levels in elderly people suffering from type 2 DM in Ngepoh Village (ρ = 0.000 < α= 0.005) So type 2 DM sufferers are expected to be able to control blood glucose, one of them is by doing AAROM Therapy and a low carbohydrate diet. AAROM therapy can reduce insulin resistance, making it easier for glucose to enter cells, preventing obesity, and improving venous blood flow.